ANALISIS TINGKAT PENGETAHUAN DAN SIKAP TENAGA KEFARMASIAN DALAM MENCEGAH OBAT RUSAK DAN KADARLUARSA DI RSUD TORA BELO - Nurul Ambianti; Muhamad Rinaldhi Tandah; Khusnul Diana; Ratu Balqis (Acta Pharmaciae Indonesia : Acta Pharm Indo, 2021)
Abstract The defective and expired drugs are one of the problems that can reflect the inaccuracy and poor of drug management in a Hospital Pharmacy Unit (HPU). This research was conducted to determine the level of knowledge and attitudes of pharmaceutical personnel in preventing defective and expired drugs at the Regional General Hospital (RGH) Tora Belo. This type of researched is a non-experimental study with cross sectional data collection. The data used are primary data obtained from the results of questionnaires that have been filled out by pharmacist at Tora Belo Hospital. The analysis used in this study is correlation analysis using the Spearman-Rho test, to determine the relationship between the level of knowledge and attitudes of pharmaceutical personnel in preventing defective and expired drugs. The number of samples is 33 people taken by total sampling. Time to collect research data during May-October 2020. From the results of the study, it is known that the level of knowledge of the respondents is dominated by the sufficient category, namely 17 respondents (71.1%), it is known that the attitude of the respondents was included in the very strong category of 18 respondents (85.78%), and the results of the correlation analysis the relationship between the level of knowledge and attitudes of pharmaceutical personnel in preventing defective and expired drugs obtained a significance value of 0.021. So it can be concluded there is a relation between the level of knowledge and attitude of pharmaceutical workers in preventing defective and expired drugs at Tora Belo Hospital.